Numerical Analysis of Air Quality Improvement and Thermal Comfort in a Classroom Using Organic Air Cleaners - Enrique Cruz-Octaviano; Guillemo Efren Ovando-Chacon; Abelardo Rodriguez-Leon; Sandy Luz Ovando-Chacon (Atmosphere, 2025)
Evaluating ventilation behavior inside classrooms in hot climates is fundamental to ensure good indoor air quality and proper thermal comfort, thus guaranteeing a healthy environment for the users. This study analyzes the impact of mixed ventilation strategies, which combine mechanical extractors and organic air cleaners (OACs), on CO2 concentration and temperature distribution in an air-conditioned classroom with closed doors and windows. We used computational fluid dynamics simulations to analyze the effect of different extractor and OACs configurations on airflow distribution and average temperature, as well as the temporal evolution of average CO2 concentrations inside the classroom. The configuration with one extractor and two OACs reduces CO2 concentrations to 613 ppm, representing an effective solution with lower energy consumption. These findings demonstrate that hybrid ventilation systems can significantly improve IAQ and maintain thermal comfort, offering viable and energy-efficient alternatives for enclosed classrooms in hot climate regions.